An investigation of learning and emerging knowledge in the Mpophomeni Sanitation Education Project, Howick, KwaZulu-Natal - Boothway, Reinetta Louina (Rhodes University, Faculty of Education, Department of Education, 2019)
This study took place within the broader context of water resources management in South Africa. With the democratisation of water stewardship through an enabling international and South African water policy landscape, an opportunity opened up for citizens to participate in the effective management of their own water resources. In this context, a community-engaged citizen science project known as the Mpophomeni Sanitation Education Project emerged to demonstrate how a diverse range of knowledge agents can work and learn together to better manage their water resources and address problems of sewage pollution threatening their provincial water source. The following study aimed to shed light on the learning and emerging knowledge in the MSEP. The study was conducted in three phases. Wenger's Communities of Practice (CoP) theory provided a lens to look at Phase One, which aimed to answer the following sub-question: Is the MSEP a CoP? Wenger's CoP theory also assisted with the investigation during Phase Two, which looked at the following question: What is the nature of learning in the MSEP? Social realist theories of knowledge and education, and TÃ bara and Chabay with their Ideal Type (IT) worldviews, provided suitable lenses for Phase Three's investigation of the following question: What is the nature of emerging knowledge in the MSEP? The main finding for Phase One is that the MSEP does function as a CoP. With its strong focus on relationships, it's clearly defined joint enterprise of solving the problem of sewage pollution, individual and joint commitment to engage with the problem and the sharing of a repertoire of tools, ideas and practices it is cultivating a culture conducive to purposeful learning. Regarding the exploration of the nature of learning in Phase Two, findings confirming the engagement of identity with learning and the importance of context for meaning-making emerged. Finally, study findings about the nature of knowledge in the MSEP found that the knowledge practices in the MSEP that are both social and epistemic in nature are produced by a diverse range of knowledge agents in an open knowledge space.
Keywords: Environmental education -- South Africa; Mpophomeni Sanitation Education Project (South Africa); Water quality management -- Study and teaching -- South Africa; Knowledge and learning